Youth Decision Making in Agricultural Adaptation to Climate Change; An Analysis in East Africa - Amsler, Kelly; Hein, Chloe; Klasek, Genêt (2017)
In conjunction with the contemporary narrative of Africa’s “youth bulge” and young people’s perceived disinterest in pursuing agricultural livelihoods, this paper explores the extent to which youth (18-35 years old) have decision making power in the implementation of agricultural adaptation practices due to climate change in East Africa via the utilization of a comparative political ecology framework. Focus groups discussions, key informant, and individual interviews were conducted with a total of 155 rural youth and 42 policymakers and stakeholder representatives in selected sites in Tanzania, Kenya, and Uganda to assess youth’s knowledge of adaptation measures and their role in the decision to implement them at the household, community, and national levels. Our findings suggest that young people have an understanding of climate change and how to adapt to it. However, they are unable to do so due to lack of agricultural inputs and financial capital, insufficient land ownership, indirect participation in decision making and limited access to markets.